1982
DOI: 10.1021/ma00229a021
|View full text |Cite
|
Sign up to set email alerts
|

Properties of low molecular weight block copolymers. 1. Differential scanning calorimetry of styrene-dimethylsiloxane diblock copolymers

Abstract: of and find that for 1200 EW polymer R = 1.4 ± 0.2 nm (22) for -1 < KJKg < 0. This value is in agreement with the value of 1.2-1.3 nm deduced from water transport experiments.2 The change in free energy that results from the formation of the channel is only -11 J/cm3; thus our elastic theory suggests the channels are continually forming and unforming at ambient temperatures. This is consistent with the previously proposed cluster-network model. V. ConclusionWe have derived a semiphenomenological expression for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 5 publications
7
56
0
Order By: Relevance
“…It should be noted that T g1 of PDMS was not obvious in S1, which was presumably due to the relatively lower PDMS content in the copolymer S1 and the relatively restricted movement of the PAPOSS blocks. Similar results have been previously reported that the detection of T g1 in the DSC curves was related to the content of PDMS in the block copolymers [28,29]. Apart from S1, the T g3 values of POSS in S2 and S3 were 84.4 • C and 82.4 • C, respectively, with each about 20 • C higher than that of S1.…”
Section: Microphase Separationsupporting
confidence: 90%
“…It should be noted that T g1 of PDMS was not obvious in S1, which was presumably due to the relatively lower PDMS content in the copolymer S1 and the relatively restricted movement of the PAPOSS blocks. Similar results have been previously reported that the detection of T g1 in the DSC curves was related to the content of PDMS in the block copolymers [28,29]. Apart from S1, the T g3 values of POSS in S2 and S3 were 84.4 • C and 82.4 • C, respectively, with each about 20 • C higher than that of S1.…”
Section: Microphase Separationsupporting
confidence: 90%
“…2, below T g B ) are relatively straight, confirming that baseline drift is not the cause of the curvature below T g S . Complications caused by the broad DSC interphase-related curvature were faced in the work of Krause et al 12,19,20 on several styrenic block copolymers. Their data were employed to assess ⌬T g S and other thermal parameters by the intersecting-tangent second-approximation method.…”
Section: Behavior Of ⌬T G and ⌬C P In Block Copolymersmentioning
confidence: 99%
“…This has been reported previously for PS-PDMS copolymers and is thought to be due to a change in the morphology from being microphase separated up to the T g,PS to a partially crystalline material. 2,3 This phenomenon was not observed for mixtures of the homopolymers PDMS and PS. 3 Electron micrograph films of PDMS-PS-PDMS triblock copolymer IV-A, whose composition was ϳ50% PS to ϳ 50% PDMS (M n ϳ 100kDa; GPC) show the formation of spherically shaped, dark PDMS microdomains embedded in a PS matrix (Fig.…”
Section: Analysis Of Experimental Resultsmentioning
confidence: 90%
“…Specifically, the electrontransfer anionic polymerization of styrene yielded telechelic PS with active anions at both ends. The addition of D 4 or D 3 to this resulted in the desired PDMS-PS-PDMS triblock copolymer. Experimentally, living anionic polymerization requires extreme care to eliminate any traces of oxygen or moisture.…”
Section: Diblock Versus Triblock Polymersmentioning
confidence: 99%
See 1 more Smart Citation